2-Methylcarbamoyl-4-{4-[3-(trifluoromethyl)benzamido]phenoxy}pyridinium 4-methylbenzenesulfonate monohydrate - Zhao Wang; Na-Na Meng; Ting-Ting Huang; Yong-Kui Zhang; Luo-Ting Yu (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C21H17F3N3O3+·C7H7O3S−·H2O, contains two formula units. In one of the cations, the pyridinium and trifluoromethyl benzene rings form dihedral angles of 87.42 (8) and 45.92 (8)°, respectively, with the central benzene ring [79.56 (8) and 43.52 (8)° in the other cation]. In the crystal structure, N—H...O, O—H...O and C—H...O hydrogen bonds link the ions and water molecules, forming a three-dimensional network.